DEVELOPING MEDIA BY USING JENGA FOR TEACHING SPEAKING TO 10TH GRADE AT SMA GAJAH MADA MEDAN - Karunia Devi Frida; Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This study aims to develop media of teaching speaking to 10th Grade at SMA Gajah Mada developed by using Jenga. The research was conducted by using developmental research, the research will be used to develop new products and procedures. This study was conducted through six phases of Research and Development (R&D) design; data collection and data collection, data analysis, material design, expert validation, revision, and final product. The data were gathered by conducting an interview to English teacher and distributing questionnaire to 22 respondents to get the students’ needs. The results of the interview and questionnaire indicate that students need English-speaking media that can inspire and enable students to speak English actively. The board game and other Jenga equipment such as blocks, dice, and cards were the result of the product. Experts have validated the products. It can be inferred that the media was valid with the maximum score was 140 for the excellent result. The results showed 92.1% or 129 from the first validator and 90% or 126 from the second validator, and it was classified as important, appropriate and possible to use as learning media for students.Keywords: Jenga for Teaching Speaking, Speaking Media, Research and Development (R&D)